Surgical Management of Thoracolumbar Burst Fractures: Surgical Decision-making Using the AOSpine Thoracolumbar Injury Classification Score and Thoracolumbar Injury Classification and Severity Score. Issue 1 (February 2021) - Morrissey, Patrick B.; Shafi, Karim A.; Wagner, Scott C.; Butler, Joseph S.; Kaye, Ian D.; Sebastian, Arjun S.; Schroeder, Gregory D.; Kepler, Christopher K.; Aarabi, Bizhan; Oner, Fetullah C.; Vaccaro, Alexander R.
Abstract : The management of thoracolumbar burst fractures is controversial with no universally accepted treatment algorithm. Several classification and scoring systems have been developed to assist in surgical decision-making. The most widely accepted are the Thoracolumbar Injury Classification and Severity Score (TLICS) and AOSpine Thoracolumbar Injury Classification Score (TL AOSIS) with both systems designed to provide a simple objective scoring criteria to guide the surgical or nonsurgical management of complex injury patterns. When used in the evaluation and treatment of thoracolumbar burst fractures, both of these systems result in safe and consistent patient care. However, there are important differences between the 2 systems, specifically in the evaluation of the complete burst fractures (AOSIS A4) and patients with transient neurological deficits (AOSIS N1). In these circumstances, the AOSpine system may more accurately capture and characterize injury severity, providing the most refined guidance for optimal treatment. With respect to surgical approach, these systems provide a framework for decision-making based on patient neurology and the status of the posterior tension band. Here we propose an operative treatment algorithm based on these fracture characteristics as well as the level of injury.